Design and validation of a robust multiplex polymerase chain reaction assay for MAT idiomorph within the Fusarium fujikuroi species complex. (3rd September 2019) - Montoya-Martínez, Amelia C.; Rodríguez-Alvarado, Gerardo; Fernández-Pavía, Sylvia P.; Proctor, Robert H.; Kim, Hye-Seon; O'Donnell, Kerry
ABSTRACT: We discovered that published polymerase chain reaction (PCR) assays for determining mating type ( MAT ) idiomorph failed to genotype some of the Fusarium fujikuroi species complex (FFSC) isolates recovered from Mangifera indica (mango), Swietenia macrophylla (big-leaf mahogany), Annona muricata (soursop), Bursera sp., and Tabebuia sp. in Mexico. Thus, the primary objective of this study was to design and validate a robust multiplex PCR–based diagnostic for typing MAT within the FFSC. To accomplish this objective, we mined the MAT1-1 or MAT1-2 locus from the genomes of 60 FFSC isolates, representing 56 phylospecies, and from four species in its sister group, the F. nisikadoi species complex (FNSC). Bioinformatic searches were facilitated by targeting DNA lyase ( SLA2 ) and apurinic endonuclease ( APN1 ), the genes that flank the MAT locus in Fusarium . As expected, three genes were identified within MAT1-1 ( MAT1-1-1, MAT1-1-2, and MAT1-1-3 ) and two in MAT1-2 ( MAT1-2-1 and MAT1-2-9 ), using the ab initio prediction tool AUGUSTUS. Of the three multiplex PCR assays we designed and tested, the one targeting MAT1-1-2 and MAT1-2-1 successfully genotyped the entire 71-isolate validation panel, which included 56 FFSC and 4 FNSC phylospecies. By contrast, the published PCR assays we tested produced positive genotypes for only 46.5–59% of the 71-isolate validation panel, but only when they were run as a uniplex assay. Although only one-fifth of the FFSC/FNSC are known to reproduce sexually, our results suggest that if they possess a sexual cycle, it is heterothallic (self-sterile).